Follow‐up of renal transplant recipients after acute COVID‐19—A prospective cohort single‐center study - Nikolina Basic‐Jukic; Ivana Juric; Vesna Furic‐Cunko; Lea Katalinic; Josipa Radic; Zrinka Bosnjak; Bojan Jelakovic; Zeljko Kastelan (Immunity, Inflammation and Disease)
Abstract Introduction Although most patients recover within several weeks after acute COVID‐19, some of them develop long‐lasting clinical symptoms. Renal transplant recipients have an increased mortality risk from COVID‐19. We aimed to describe complications occurring after COVID‐19 in this group of patients. Methods A prospective single‐center cohort study was conducted at University Hospital Centre Zagreb. Patients with two negative reverse transcriptase‐polymerase chain reaction (RT‐PCR) tests for SARS‐CoV‐2 after COVID‐19 were eligible for further follow‐up at our outpatient clinic. They underwent detailed clinical and laboratory assessments. The primary outcome was the development of complications after COVID‐19. Results Only 11.53% of renal transplant recipients who survived acute COVID‐19 were symptomless and free from new‐onset laboratory abnormalities during the median follow‐up of 64 days (range: 50–76 days). Three patients died from sepsis after discharge from the hospital. In 47 patients (45.2%), clinical complications were present, while 74 patients (71.2%) had one or more laboratory abnormalities. The most common clinical complications included shortness of breath (19.2%), tiredness (11.5%), peripheral neuropathy (7.7%), self‐reported cognitive impairments (5.7%), and dry cough (7.7%). Most common laboratory abnormalities included shortened activated partial thromboplastin time (50%), elevated D‐dimers (36.5%), elevated fibrinogen (30.16%), and hypogammaglobulinemia (24%). Positive RT‐PCR for cytomegalovirus (8.7%), Epstein–Barr virus (26%), or BK virus (16.3%). Multivariate analysis identified the history of diabetes mellitus and eGFR CKD‐EPI as predictors for the development of post‐COVID clinical complications. Six months after acute COVID‐19, elevated D‐dimers persisted with normalization of other laboratory parameters. Twenty‐nine patients were hospitalized, mostly with several concomitant problems. However, initially reported clinical problems gradually improved in the majority of patients. Conclusion Post‐COVID‐19 clinical and laboratory complications are frequent in the renal transplant population, in some of them associated with significant morbidity. All patients recovered from acute COVID‐19 should undergo long‐term monitoring for evaluation and treatment of complications.